Circulating tumor DNA is a sensitive marker for routine monitoring of treatment response in advanced colorectal cancer. (21st September 2020) - Zou, Donghui; Day, Robert; Cocadiz, Judy A; Parackal, Sarah; Mitchell, Wilson; Black, Michael A; Lawrence, Ben; Fitzgerald, Sandra; Print, Cristin; Jackson, Christopher; Guilford, Parry
Abstract: Accurate assessment of chemotherapy response provides the means to terminate ineffective treatment, trial alternative drug regimens or schedules and reduce dose to minimize toxicity. Here, we have compared circulating tumor DNA (ctDNA) with carcinoembryonic antigen (CEA) for the cycle by cycle assessment of chemotherapy response in 30 patients with metastatic colorectal cancer. CtDNA (quantified using individualized digital droplet PCR (ddPCR) assays) and CEA levels were determined immediately prior to each chemotherapy cycle over time periods ranging from 42–548 days (average of 10 time points/patient). Twenty-nine/thirty (97%) patients had detectable ctDNA compared with 83% whose tumors were CEA-positive (>5 ng/ml) during the monitoring course. Over the course of treatment, 20 disease progression events were detected by computed tomography; ctDNA predicted significantly more of these events than CEA (16 (80%) versus 6 (30%), respectively; P- value = 0.004). When progression was detected by both ctDNA and CEA, the rise in ctDNA occurred significantly earlier than CEA ( P- value = 0.046). Partial responses to chemotherapy were also detected more frequently by ctDNA, although this was not significant ( P- value = 0.07). In addition, another 28 colorectal cancer patients who underwent potentially curative surgery and showed no evidence of residual disease were monitored with ctDNA for up to 2 years. Clinical relapse was observed in 6/28 (21%) patients. Four out of 6 of these patients showed a significant increase in ctDNA at or prior to relapse. Overall, ctDNA analyses were able to be performed in a clinically relevant timeline and were a more sensitive and responsive measure of tumor burden than CEA. Abstract : In a prospective series of 572 plasma samples collected from 58 stage II–IV colorectal cancer patients, circulating tumour DNA detected disease progression earlier and more frequently than carcinoembryonic antigen and was more responsive to changes in treatment.